Implementation of a Cooperative Learning Model of Group Investigation Type to Increase Student Activity and Understanding of Tayyibah Hauqalah Sentence Material - Munif, Moh. Vito Miftahul (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
This research aims to implement a group investigation type cooperative learning model to increase student activity and the level of student understanding of the tayyibah hauqalah sentence material. This research method uses the type of Classroom Action Research (PTK). The PTK model used refers to Kurt Lewin, which has a spiral shape from cycle I to cycle II. Each cycle consists of planning, action, observation, and reflection. Data collection techniques in this research used observation, interviews, documentation and tests. The data analysis technique in this research uses descriptive statistical analysis techniques to analyze quantitative data. The results of this research show that 1) there is an increase in student activity, as evidenced by the results of observations of student learning activity in cycle I which shows that the score obtained is 80 out of a maximum score of 92, or if the final score of student activity obtained is 90% of maximum score. Furthermore, in cycle II there was also an increase in student learning activity, as evidenced by the results of observations of student learning activity, which obtained a score of 86 out of a maximum score of 92, or if the final score of student activity was obtained as a percentage, it was 93% of the maximum score. 2) there was an increase in the level of students' understanding of the tayyibah hauqalah sentence material in cycle I as evidenced by students getting an average class score of 80.0 and the percentage of learning completion that reached the KKM was 76% or 23 students. Furthermore, in cycle II there was also an increase in the level of students' understanding of the tayyibah hauqalah sentence material as evidenced by students getting an average class score of 88.5 and the percentage of learning completion that reached the KKM was 93% or as many as 28 students.